Chinese visions of self and Other: The international politics of noses - CALLAHAN, William A. (Institutional Knowledge at Singapore Management University, 2023)
How does China view the world? While much has been written about how China's international relations are best seen as intercultural relations that do not exclude the Other, this article examines how self/Other relations are visualized in terms of the human face in China, in particular through iconic images that construct the Chinese self with and against foreigners with large noses. It employs interpretivist methods to consider the interplay of social relations and international relations in order to see how ‘external appearance’ and ‘external relations’ inform each other in Chinese theory and practice. It mobilizes the classical Chinese concept ‘deep-set eyes and high-bridged nose’ to compare iconic Chinese images of noses from the Tang dynasty, the Korean War, and twenty-first century China and Taiwan. This critical juxtaposition shows how foreigners are visualized as both friends and enemies in a hierarchical social system. The article's use of visual International Relations (IR) methods enables us to re-examine foreign affairs as a site of affective politics, and thus appreciate how China's ideological world-view resonates with how its artists, scholars and officials aesthetically view the world. This is a concern for IR scholars because world-views shape how foreign policy-makers frame foreign policy problems—and thus foreign policy solutions.